2021
DOI: 10.3390/foods10040740
|View full text |Cite
|
Sign up to set email alerts
|

Germinated Buckwheat: Effects of Dehulling on Phenolics Profile and Antioxidant Activity of Buckwheat Seeds

Abstract: The aim was to investigate the effects of the cold dehulling of buckwheat seeds on their germination, total phenolic content (TPC), antioxidant activity (AA) and phenolics composition. Cold dehulling had no negative effects on germination rate and resulted in faster rootlet growth compared to hulled seeds. Although the dehulling of the seeds significantly decreased TPC and AA, the germination of dehulled seeds resulted in 1.8-fold and 1.9-fold higher TPC and AA compared to hulled seeds. Liquid chromatography c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 59 publications
3
21
0
Order By: Relevance
“…Earlier studies have shown that the DPPH radical-scavenging activity may be attributed to the fact that the amount of flavonoid ingredients and phenolic acid significantly increased during common buckwheat germination ( 43 ), the DPPH assay were strongly correlated to the content of total phenolic acids and proanthocyanidins level in the cotyledons ( 44 ). The results of ABTS radical-scavenging activity were essentially the same as those obtained by Živković Andrej's study ( 45 ), compared with phenolic content, the antioxidant activity (DPPH and ABTS) measures showed similar trends during the course of germination. However, the changes in flavonoids and phenolic acid monomers and the relevance to the antioxidant properties of sprouts were not studied, so in future studies, the effect of PAW on antioxidant activity in buckwheat sprouts can be considered by targeted metabolomics and analyze the intrinsic mechanism, and improve the study of changes in relevant enzymes in parallel with a view to provide a basis for their nutrient changes.…”
Section: Discussionsupporting
confidence: 84%
“…Earlier studies have shown that the DPPH radical-scavenging activity may be attributed to the fact that the amount of flavonoid ingredients and phenolic acid significantly increased during common buckwheat germination ( 43 ), the DPPH assay were strongly correlated to the content of total phenolic acids and proanthocyanidins level in the cotyledons ( 44 ). The results of ABTS radical-scavenging activity were essentially the same as those obtained by Živković Andrej's study ( 45 ), compared with phenolic content, the antioxidant activity (DPPH and ABTS) measures showed similar trends during the course of germination. However, the changes in flavonoids and phenolic acid monomers and the relevance to the antioxidant properties of sprouts were not studied, so in future studies, the effect of PAW on antioxidant activity in buckwheat sprouts can be considered by targeted metabolomics and analyze the intrinsic mechanism, and improve the study of changes in relevant enzymes in parallel with a view to provide a basis for their nutrient changes.…”
Section: Discussionsupporting
confidence: 84%
“…SPE based on reversed-phase polymeric sorbents allows the extraction of phenolics and the removal of sugars and other highly polar compounds (e.g., organic acids, amino acids, proteins) [10]. Many studies have focused on the extraction and SPE purification of the extractable phenolics from cereals [11][12][13][14][15] and reported that SPE clean-up step allows high recoveries and good precision for extractable phenolic acids in a different cereals. To the best of our knowledge, the application and optimisation of SPE for the extraction and purification of bound phenolics extracts has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The buckwheat plant is easily adaptable, so that it can be grown almost anywhere in the world and different habitats, from high altitude regions, with low rainfall and temperatures, even in nutrient-poor soils and has a higher resistance to pests in compared to other cereals [ 43 , 50 , 51 ].…”
Section: Buckwheat and Amaranth: Raw Materials For Brewingmentioning
confidence: 99%
“…The consumption of products containing buckwheat have a hypoglycaemic, hepatoprotective, anticancer, antihemorrhagic, anti-inflammatory, antioxidant, vasoprotective, antihypertensive, and cytoprotective effect, reduces the total triglycerides and total cholesterol in serum and liver, blood sugar, and blood pressure, prevents cardiovascular disease gallstones and cognitive impairments such as Alzheimer’s disease [ 40 , 41 , 54 , 56 ]. It can also lead to weight loss as well as a lower risk of diabetes, stroke, and coronary heart disease [ 51 , 57 ]. Soluble and insoluble dietary fibre in buckwheat grains positively affects constipation and obesity [ 58 ].…”
Section: Buckwheat and Amaranth: Raw Materials For Brewingmentioning
confidence: 99%
See 1 more Smart Citation